1983
DOI: 10.1017/s0022112083003195
|View full text |Cite
|
Sign up to set email alerts
|

Noise generation by a low-Mach-number jet

Abstract: Using a ‘clean’ jet facility the relationship between the jet flow and its radiation field was studied experimentally in the Mach-number range 0.05 < Mj < 0.20 and a Reynolds-number range 6 × 104 < ReD < 2.3 × 105. The various acoustic source parameters such as strength, frequency and Mach number were varied systematically, and the far-field pressure measured simultaneously. On the basis of these measurements the nature of the sources in the initial shear layer could be characterized. The principal results, eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
87
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 17 publications
15
87
1
Order By: Relevance
“…It gave a superdirective radiation pattern, which replicated some earlier subsonic jet experiments of Laufer & Yen (1983) and has since been observed in several numerical studies of unsteady laminar shear flows, forced so as to produce vortex pairing. For example, Colonius, Lele & Moin (1997) imposed disturbances on a two-dimensional plane mixing layer at the fundamental (most unstable) frequency and two subharmonics.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…It gave a superdirective radiation pattern, which replicated some earlier subsonic jet experiments of Laufer & Yen (1983) and has since been observed in several numerical studies of unsteady laminar shear flows, forced so as to produce vortex pairing. For example, Colonius, Lele & Moin (1997) imposed disturbances on a two-dimensional plane mixing layer at the fundamental (most unstable) frequency and two subharmonics.…”
Section: Introductionsupporting
confidence: 83%
“…The weakly nonlinear interactions studied here fall into this category since the primary instability mechanism is vortical. Quadratic nonlinearity of a similar type was also apparent in the experiments of Laufer & Yen (1983), for forced vortex pairing in a round jet. They observed that the sound intensity varied as the fourth power of the near-field mode saturation amplitude, whereas a second power would be expected for a linear relationship of the type assumed in the Huerre & Crighton (1983) model.…”
Section: Discussionmentioning
confidence: 62%
“…17 Note also that to the best of our knowledge, no other experimental work has been published since the work of Bridges & Hussain 14 to investigate the directivity and the location of the extinction angle in excited jets. In the present work, the two radiation patterns were recovered in the same facility to avoid usual criticisms, such as a possible artefact introduced by the nozzle in the Laufer & Yen experiment.…”
Section: Motivation and Goalsmentioning
confidence: 98%
“…The documented experimental work on subsonic jets concern measurements focusing either on properties of the flow field or on properties of the acoustic far field. Turbulence characteristics of subsonic turbulent jets with a moderate to high Reynolds number (Re ≈ 10 3 −10 5 ) were reported by Panchapakesan & Lumley [24], Hussein et al [12], Zaman [40], Wygnanski & Fiedler [38], Laufer and Yen [15] and Bradshaw et al [7]. Most of the work mentioned concerned low velocity jets (Ma<0·3), and do not or briefly discuss properties of the acoustic far field.…”
Section: Introductionmentioning
confidence: 99%